Fűz és nyár avar lebontásának vizsgálata a Balaton és a Kis-Balaton területén - Koók, Viktor; Simon, Brigitta; Kucserka, Tamás (GEORGIKON FOR AGRICULTURE, 2018)
Salix sp. and Populus sp. forests are found throughout Hungary along major rivers and lakes. During the fall there is a significant amount of leaf litter getting into these waters. The leaves in our waters contribute significantly to the loading of organic matter, therefore the exploration and understanding of decompostion is essential. Leaf litter bag method was used with two mesh sizes in this observation.  In our study, during the winter season, the Salix sp. leaf degradation was found to fall into the fast and the Populus sp. into the medium decomposition category in the case of Lake Balaton and both leaves fall into the middle decomposition category in the case of Kis-Balaton Wetland. In contrast, in the summer both Lake Balaton and Kis-Balaton’s leaf degradation fell into the fast decomposition category.
Keywords: leaf litter decompposition; salix sp; populus sp; litter bag; Balaton; Kis-Balaton Wetland